CORPORATE CULTURE AS A MODEL OF INNOVATIVE DEVELOPMENT OF AN EDUCATIONAL ORGANIZATION - BILYK, Viktoriia; HRYHORIEVA, Olha; DUMANETSKYI, Viacheslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores corporate culture as a key model for the innovative development of an educational organization under conditions of globalization, digital transformation, and increasing societal demands for the quality of educational services. The relevance of the study is determined by the need to form competitive educational institutions capable of effectively adapting to dynamic environmental changes, ensuring academic integrity, and fostering the creative and intellectual potential of participants in the educational process. The paper summarizes theoretical approaches to defining the essence of corporate culture and identifies its specific features within educational organizations. It is substantiated that corporate culture in education performs not only regulatory and integrative functions but also acts as a strategic resource for innovative transformation. The main components of corporate culture in an educational organization are analyzed, including value systems, norms and behavioral rules, communication mechanisms, leadership practices, symbolism, and traditions, as well as their influence on organizational identity formation. Special attention is paid to the role of leadership and communication in shaping openness to change, implementing digital technologies, innovative pedagogical methods, and developing partnership relations. An innovative model of corporate culture formation in an educational organization is proposed, characterized by a multi-level structure that integrates value-based, normative-organizational, communication, leadership, and innovation dimensions. The study concludes that a coherent and innovation-oriented corporate culture serves as a foundation for the sustainable development of educational organizations, enhancing their competitiveness and improving the quality of educational services in the context of digitalization and global challenges.